A tailored systems engineering process for developing student-built CubeSat class satellites - Gregory, John M., author; Sega, Ronald M., advisor; Borky, John M., advisor; Bradley, Thomas, committee member; Yalin, Azer, committee member (Colorado State University. Libraries, 2025)
This research seeks to develop a novel model-based systems engineering approach that is informed by students, subject matter experts, and instructors through an iterative process. The approach will be tailored to the capabilities, time constraints, and resources typical of undergraduate space systems design and development courses and is likely to be extensible to other organizations with similar constraints in time and other resources. This research was motivated by the rise in prevalence of CubeSats in the education space. CubeSats have become an important element of space systems engineering education and research activities across the globe. A variety of universities and government stakeholders have developed educational materials and coursework to train students to follow systems engineering processes in developing these systems, but these materials generally recommend that students follow traditional, professionally-derived systems engineering processes without acknowledging the technical and managerial limitations of the workforce in an undergraduate learning environment. The considerations for and procedures followed to develop these systems engineering processes included the use of iterative stakeholder surveys across multiple academic years and are presented here. The results of implementation of these processes in successive cohorts of undergraduate students performing CubeSat design and development are presented. The results show a significant improvement in instructor and subject matter expert-assessed student learning and student performance when compared with students who did not utilize systems engineering techniques. The causes of these results are elucidated with evidence of improved understanding of the systems engineering process, and improved cohort-to-cohort information flow. It is expected that when more data is available, there will be an improvement in the satellite system performance when the process developed in this dissertation is used in the design, build and operations of a CubeSat. The Systems Engineering Handbook developed through this study is available for other educators and students in Appendix B of this dissertation and at https://hdl.handle.net/10217/237534.
Keywords: engineering education; systems engineering; CubeSat; tailored; MBSE